A first worldwide multispecies survey of invasive Mediterranean pine bark beetles (Coleoptera: Curculionidae, Scolytinae) - Faccoli, Massimo (2020)
Several European and Mediterranean species of pine bark beetles (Coleoptera: Curculionidae: Scolytinae) have become established in North America and the southern hemisphere, posing a novel threat to planted and naturally-occurring pine forests. Our objectives were to investigate (1) the occurrence and relative abundance of pine bark beetles in these regions, and (2) the trapping performance of different blends of multispecies lures. In 2016–2017 a network of interception traps was installed in six non-European countries (Argentina, Australia, New Zealand, South Africa, the United States, and Uruguay), and in six European countries (France, Greece, Hungary, Italy, Portugal, and Spain) for comparison. Half of the traps were baited with alpha-pinene and ethanol, and the other half with alpha-pinene, ethanol, and a combination of bark beetle pheromones (ipsdienol, ipsenol, and Z-verbenol). Five Mediterranean scolytine species (Hylurgus ligniperda, Hylastes ater, H. angustatus, Orthotomicus erosus, and O. laricis) were found in non-European countries. Hylurgus ligniperda and Hylastes ater were the most widespread species found in several of the invaded regions, while O. laricis and H. angustatus occurred only in Argentina and South Africa, respectively. Despite large variation among species and countries, most species were trapped with the blend containing bark beetle pheromones, except O. erosus, which was more attracted to alpha-pinene and ethanol alone. This study represents the first step towards the development of an international monitoring protocol based on multi-lure traps for the survey and early-interception of invasive alien bark beetle species.